Level of physical activity of the Portuguese and French students in physiotherapy course - Costa, A. (2021)
Physical activity (PA) comprises any kind of energetic expenditure above the stationary level and it is associated to the well being, life quality and health enhancement. Nowadays, he practice of PA is tending to decrease among university students. It is imperative that those students have the base concepts of PA and healthy habits so that they can alert and modify the community habits and mindsets in the future.